PENGALAMAN KOMUNIKASI DAN KONSEP DIRI PENGUNGSI ASAL AFGHANISTAN DI KECAMATAN RUMBAI - Febi Yadani. S; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Immigration is the movement of people from one country to another. Many factors cause immigration to occur. Refugees as people who take human rights protection to other countries and wait for a third country. Indonesia is one of the destinations for asylum seekers and refugees, and Pekabaru is one of the refugee shelters. Afghan refugees are the largest refugees in Pekanbaru and In Rumbai District. The existence of inhibiting interaction with local community and refugees one of them difference of language. The negative public view of the refugeesThe type of research is descriptive qualitative with phenomenology approach. Based on field facts through observation, interview and documentation. Research subjects are some Afghan refugees in Rumbai District are 4 people who have been in Pekanbaru at 1-4 years in Refugee status. This study focuses on exploration in the informant's communication experience. For the purposes of this study are proposed the following three questions: (1) What is the experience of Afghan refugee communication in Rumbai Sub-district (2) What is the Afghan refugee self image in Rumbai District (3) What is the Afghan refugee self-esteem in Rumbai District.The results of this research show that communication experience is categorized into two, ie, enjoyable communication experience and unpleasant communication experience. The self-image of Afghan refugees is both positive and negative, reflected in their self-image, self-image, personality, self as refugees and self-reliance on the basis of others. Afghan refugees' self-esteem from four informants, three have positive self-esteem and one person has negative self-esteem.Keywords: Refugees, Communication Experience, Self Image, Self Esteem